MMP‐13 binds to platelet receptors αIIbβ3 and GPVI and impairs aggregation and thrombus formation. Issue 2 (25th March 2018) - Howes, Joanna‐Marie; Pugh, Nicholas; Hamaia, Samir W.; Jung, Stephanie M.; Knäuper, Vera; Malcor, Jean‐Daniel; Farndale, Richard W.
Abstract: Essentials MMP‐13 has the potential to influence platelet function and thrombus formation directly. We sought to elucidate whether MMP‐13 is able to bind to specific platelet receptors. MMP‐13 is able to bind to platelet alphaIIbbeta3 (αIIbβ3) and glycoprotein (GP)VI. These interactions are sufficient to inhibit platelet aggregation and thrombus formation. Background: Acute thrombotic syndromes lead to atherosclerotic plaque rupture with subsequent thrombus formation, myocardial infarction and stroke. Following rupture, flowing blood is exposed to plaque components, including collagen, which triggers platelet activation and aggregation. However, plaque rupture releases other components into the surrounding vessel which have the potential to influence platelet function and thrombus formation. Objectives: Here we sought to elucidate whether matrix metalloproteinase‐13 (MMP‐13), a collagenolytic metalloproteinase up‐regulated in atherothrombotic and inflammatory conditions, affects platelet aggregation and thrombus formation. Results: We demonstrate that MMP‐13 is able to bind to platelet receptors alphaIIbbeta3 (αIIbβ3) and platelet glycoprotein (GP)VI. The interactions between MMP‐13, GPVI and αIIbβ3 are sufficient to significantly inhibit washed platelet aggregation and decrease thrombus formation on fibrillar collagen. Conclusions: Our data demonstrate a role for MMP‐13 in the inhibition of both platelet aggregation and thrombus formation in whole flowing blood, and may provide new avenues of research into the mechanisms underlying the subtle role of MMP‐13 in atherothrombotic pathologies.